An assessment of mortality among elderly brazilians from alcohol abuse diseases : a longitudinal study from 1996 to 2019 - Barbosa, João de Sousa Pinheiro (2022)
Alcohol use disorder (AUD) is a worldwide public health problem, being an important aggravating factor of comorbidities found in the elderly, with the potential to increase mortality indicators for this age group. Objective: To analyze alcohol-induced deaths in elderly people with alcohol-related disorder in Brazil between 1996 and 2019. Methods: An ecological study was conducted with secondary data obtained from the Brazilian Unified Health System (SIM) Mortality Information System from 1996 to 2019. TabNet/DATASUS, Excel® 2016 and SPSS 21® were used to prepare the results. Results: Between 1996 and 2019, 85,928 alcohol-induced deaths were recorded among the elderly (>60 years); in 1996, the lowest number of deaths was recorded (n = 1396), and in 2018, there were the highest number of deaths (n = 5667). In the profile of the elderly, there was a predominance of men (88%). Mortality from AUD was due to alcoholic liver disease (62.2%), followed by mental disorders due to alcohol use (37.3%). Conclusions: Coping with AUD is a public health problem that aims to reduce the number of deaths from diseases, conditions and injuries in which alcohol consumption is the causative agent, in addition to preventing deaths to which alcohol contributes.